Implementing hybrid automata for developing industrial control systems - Hien, N.-V.; Soriano, T. (IEEE International Conference on Emerging Technologies and Factory Automation 2001, 2001)
We propose a method, which is based on capsules, ports, protocols and entity classes to implement a hybrid automaton with input or output events and signals in order to quickly identify and implement control objects of an industrial control system. This method also supports control systems to be re-used in the new application design phase. We introduce step-by-step specification activities of a hybrid automaton such as the identification of principle control capsules, their ports and communication protocols, with their static and dynamic links which unify them. Then, we introduce important hypotheses which allow all the identified capsules of this system to make their evolutions. We applied this method to develop a sweeping camera control system which is a part of the person detection device by video.